INOVASI VERTIKULTUR BERBASIS DAUR ULANG BOTOL PLASTIK SEBAGAI UPAYA MENDUKUNG HILIRISASI KETAHANAN PANGAN DI LAHAN TERBATAS - Anggun Wulandari; Umi Kulsum Nur Qomariah; Kartika Wulandari (Universitas Mataram, 2025)
Environmental problems caused by the increase in household plastic waste, particularly single-use plastic bottles, have become a serious issue in Betek Village, Mojoagung, Jombang. An average of 4–5 kg of plastic bottles is collected every week at the Betek Bersinar Waste Bank, with suboptimal utilization. This condition demands innovation in productive and sustainable management through vertical farming based on plastic waste recycling. This community service program aims to empower the community through the implementation of vertical farming based on plastic bottle recycling as an effort to downstream food security in limited land. The implementation method uses a participatory approach through the stages of preparation, education and counseling, technical training, implementation and mentoring, and evaluation & monitoring. The activity evaluation uses a pretest–posttest one-group design with 18 participants consisting of waste bank managers and village officials. The evaluation instrument is a Likert questionnaire 1–5 to measure the participants' management skills. The results show an increase in management skills from 58.67% to 83.61%, with the category of